Zakat, Islamic Economics And Poverty Alleviation In Indonesia - Linda Wahyu Marpaung (Proceeding International Seminar of Islamic Studies, 2019)
: Indonesia is a country with a majority Muslim population. The total Muslimpopulation is 209.12 million people or 87% of the total 269 million people with a total poor population of 9.41% or 25.14 million people. In 2018 the amount of zakat collected was as much as Rp. 8.100 billion with a potential of Rp 217 Trillion. Poverty is a problem that seizes the attention of the government every year. With the majority of the Islamic population, zakat is one solution to reduce poverty. The purpose of this study is to determine the potential for poverty alleviation with zakat and the opportunity for Indonesia to become the center of Islamic economics. The method used is the study of literature, namely data collection techniques by conducting a study of a review of books, literature, notes, and journals that are in accordance with the research objectives. Basically, zakat aside from being a form of obedience to God is also a social concern. The concept of zakat in Islam is mandatory and is the identity and characteristics of Islamic economics that distinguish it from conventional economic systems. Zakat is an Islamic economic joint, which if implemented properly, will have a significant economic impact. Through proper, transparent, and professional distribution zakat should be an alternative in alleviating poverty in Indonesia.